Effectiveness of Flipped Learning Method in Improving Students’ Speaking Skill - Rina Marliana (Institut Agama Islam Negeri Palopo, 2022)
This research aim to find out the effectiveness of using the flipped learning method in improving students’ speaking skill. This research employed quasi-experimental method. The subject of this research were two groups, the experimental and the control group of the third semester students of Tadris Bahasa Inggris STAIN Majene. The data of this research were collected through pretest and post-test. The data of this research were analyzed by using SPSS. The result of the research reveal that the students’ post-test in experimental experiment class, the minimum results were 20 and the maximum score was 60 with an average score of 32,00. While in the control class, after the researcher gave an pre-test, the score was 20 and the maximum value was 44 with an average value of 33,71. And then, the researcher gave a post-test without doing treatment, the result of the minimum score was 20 and the maximum score was 60, so the average score was 37,33. The increasing of the value after the experiment class being given a treatment from the average value 24,57 to 32,00. The mean result for the experimental class is -7.429, with a standard deviation of 6.727 so that H1 is accepted because the value of sig < Alpha or 0.000 < 0.005. Based on these data, it can be concluded that there is a difference in the average learning outcomes of students in the experimental class using the flipped learning method to improve their speaking skills.Key words: Flipped learning, speaking skill